Fragile Conviction Changing Ideological Landscapes in Urban Kyrgyzstan - Pelkmans, Mathijs (Cornell University Press, 2017)
How does ideology function during periods of political and economic turmoil? This book, based on long-term ethnographic research in a destitute former mining town in Kyrgyzstan, testifies to the precariousness of life in the former Soviet republics in the decades after the collapse of the USSR. It follows inhabitants as they make sense of a radically changing world and as they try to imbue their lives with relevance and direction, while concentrating in depth on their engagement with a range of religious ideas and other ideological currents, including scientific atheism, evangelical Christianity, Sunni Islamic revivalism, and traditional shamanistic beliefs. By examining such a broad variety of belief systems and how they manifest themselves in daily life, the author provides new insights into how ideology works (or fails to work) and how cultural and religious convictions are collectively produced and shaped.